New Imaging Strategies Using a Motion-Resistant Liver Sequence in Uncooperative Patients. (27th August 2014) - Kim, Bong Soo; Lee, Kyung Ryeol; Goh, Myeng Ju
Abstract : MR imaging has unique benefits for evaluating the liver because of its high-resolution capability and ability to permit detailed assessment of anatomic lesions. In uncooperative patients, motion artifacts can impair the image quality and lead to the loss of diagnostic information. In this setting, the recent advances in motion-resistant liver MR techniques, including faster imaging protocols (e.g., dual-echo magnetization-prepared rapid-acquisition gradient echo (MP-RAGE), view-sharing technique), the data under-sampling (e.g., gradient recalled echo (GRE) with controlled aliasing in parallel imaging results in higher acceleration (CAIPIRINHA), single-shot echo-train spin-echo (SS-ETSE)), and motion-artifact minimization method (e.g., radial GRE with/without k-space-weighted image contrast (KWIC)), can provide consistent, artifact-free images with adequate image quality and can lead to promising diagnostic performance. Understanding of the different motion-resistant options allows radiologists to adopt the most appropriate technique for their clinical practice and thereby significantly improve patient care.